Assembly mistakes of steel structures - Litwin, Małgorzata; Górecki, Marcin (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
Steel structures have plenty of advantages, which decide on their usage in many buildings. At the same time require they great precision in the design stage as well as during the building phase. Indispensable precision is oft a reason for design and assembly mistakes. In the paper there are presented the assembly mistakes, which occur the most often during the realisation stage.